Bringing Variable Renewable Energy Up to Scale : Options for Grid Integration Using Natural Gas and Energy Storage - Martinez Romero, Silvia (World Bank Group, Washington, DC, 2015)
By the end of 2013, 144 countries both developed and developing had established plans for the expansion of power generation from renewable energy (REN 21). In setting these goals, countries are driven by a number of strategic considerations, including energy security, reducing pollution and greenhouse gas emissions, the need to expand and improve energy services for growing populations, and industrialization and job creation. Among renewable energy sources, solar and wind resources stand out as having high inherent resource variability and limited predictability. To achieve a reliable, stable power supply, power system operators must continuously balance supply and demand. Power systems are designed to handle a certain amount of variability and uncertainty to accommodate fluctuations in demand and unexpected equipment outages. This report looks at the nature of Variable Renewable Energy (VRE) and the resulting challenges associated with the integration of VRE technologies into a power system. It provides an overview of the measures available to limit and manage these challenges. This report highlights the importance of increased flexibility when integrating high levels of VRE, and focuses on two sets of options to provide such flexibility: natural gas-fired power generation technologies and energy storage. Finally, this report provides some insight into the implications of VRE expansion for planning and regulation, and finishes with some recommendations for planners and policy makers. Topics included in this report also include: natural gas as an option for supply flexibility, energy storage as an option for flexibility, and planning and policy considerations. Findings include the realization that to best manage the challenge of integrating higher levels of VRE into electricity grids, policy, planning and regulatory interventions should be designed to minimize overall system costs and that the value of flexibility in the system should be recognized through policy and regulation, and remuneration mechanisms for flexible capacity should be defined.